Mapping the nanomechanical properties of graphene suspended on silica nanoparticles. Issue 13 (1st September 2016) - Osváth, Z.; Gergely-Fülöp, E.; Deák, A.; Hwang, C.; Biró, L.P.
ABSTRACT: Using nanoparticles to impart extrinsic rippling in graphene is a relatively new method to induce strain and to tailor the properties of graphene. Here, we study the structure and elastic properties of graphene grown by chemical vapour deposition and transferred onto a continuous layer of SiO2 nanoparticles with diameters of around 25 nm, prepared by Langmuir–Blodgett technique on Si substrate. We show that the transferred graphene follows only roughly the morphology induced by nanoparticles. The graphene membrane parts bridging the nanoparticles are suspended and their adhesion to the atomic force microscope tip is larger compared to that of supported graphene parts. These suspended graphene regions can be deformed with forces of the order of 10 nN. The elastic modulus of graphene was determined from indentation measurements performed on suspended membrane regions with diameters in the 100 nm range.